2021
DOI: 10.4103/ijnmr.ijnmr_32_20
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk in Women with High Risk Pregnancy

Abstract: Background: Risk perception in high-risk pregnancies influences the mothers' adherence to medical treatments and recommendations. Because of the lack of information about the women's perception of risk, the aim of this study was to explain perception of risk in high-risk pregnancies. Materials and Methods: This qualitative study was conducted on 25 women with a high-risk pregnancy in educational hospitals of Mashhad, Iran, from August 2017 to August 2018. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…In recent years, high-risk pregnancy has become increasingly common in the clinic, accounting for 8–12% of all pregnancies, an approximately four-fold increase compared to 2010 [ 2 ]. High-risk pregnancy not only poses a great threat to the newborn but may also lead to maternal death due to shock and massive hemorrhage during delivery [ 3 ]. Therefore, in clinic, it is necessary to focus on monitoring and additional targeted treatment for such pregnant women, so as to ensure maternal and child safety.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high-risk pregnancy has become increasingly common in the clinic, accounting for 8–12% of all pregnancies, an approximately four-fold increase compared to 2010 [ 2 ]. High-risk pregnancy not only poses a great threat to the newborn but may also lead to maternal death due to shock and massive hemorrhage during delivery [ 3 ]. Therefore, in clinic, it is necessary to focus on monitoring and additional targeted treatment for such pregnant women, so as to ensure maternal and child safety.…”
Section: Introductionmentioning
confidence: 99%
“…Study ( 17 ) carried out with GAR in teaching hospitals in Iran showed that these pregnancies are accompanied by many sensations and profound changes in the mental structure, influenced by perceptions, expectations and previous experiences, requiring adaptation strategies in the context in which the risk occurs.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the diagnosis of HRP, as well as the experience of a borderline situation between life and death, brings a feeling of fear and loneliness caused by stress, and the perception of risk is effective in the attitude towards the treatment, maternal decisions in pregnancy and adherence to medical procedures and recommendations ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Estudo (17) realizado com GAR em hospitais de ensino no Irã mostrou que essas gestações são acompanhadas por muitas sensações e profundas modificações na estrutura mental, influenciadas por percepções, expectativas e experiências anteriores, requerendo estratégias de adaptação no contexto em que ocorre o risco.…”
Section: Discussão Categoria 1: Saberes E Significados Atribuídos à G...unclassified